2005
DOI: 10.1007/s00423-004-0521-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for multinodular goitres in geriatric patients

Abstract: MG operated on in elderly patients has a longer evolution and an intrathoracic component, and surgery is indicated restrictively. With close monitoring of the co-morbidities and a programmed operation the results with regard to morbidity and mortality are similar to those obtained at younger ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
1
27
1
Order By: Relevance
“…The ratio of signal enhancement to noise (SE/N) was calculated as defined by Inoue et al, 13 as follows: SE/N=(S post −S pre )/NSD), where S post is signal intensity after injection, S pre is signal intensity before injection, and NSD is standard deviation of the background. Timeintensity curve patterns reflected the following 3 patterns of contrast enhancement: (1) delayed washout pattern in which the timeintensity curve was less than half of peak grade during 10 minutes (Figure 1 and Figure 2), (2) rapid washout pattern in which the time-intensity curve was less than half of peak grade within 10 minutes (Figure 3), and (3) no contrast enhancement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of signal enhancement to noise (SE/N) was calculated as defined by Inoue et al, 13 as follows: SE/N=(S post −S pre )/NSD), where S post is signal intensity after injection, S pre is signal intensity before injection, and NSD is standard deviation of the background. Timeintensity curve patterns reflected the following 3 patterns of contrast enhancement: (1) delayed washout pattern in which the timeintensity curve was less than half of peak grade during 10 minutes (Figure 1 and Figure 2), (2) rapid washout pattern in which the time-intensity curve was less than half of peak grade within 10 minutes (Figure 3), and (3) no contrast enhancement.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 The presence of a dominant cold nodule in a thyroid gland with multiple nodules is an important risk factor associated with thyroid carcinoma. 3 Differentiation of a benign thyroid nodule from a malignant thyroid nodule is important in planning the further therapeutic approach and the extent of surgical intervention.…”
Section: T He Primary Indications Formentioning
confidence: 99%
“…In our study we observed a significant higher rate of tracheal compressive symptoms in the elderly. Even higher rates were reported by Rios et al [17], who noted a correlation of compressive symptoms with longer time of goiter evolution and higher percentage of an intrathoracic component. Consequently, their older patients treated for multinodular goiter had a longer duration of surgery, more intraoperative blood loss, and larger resected thyroid glands.…”
Section: Discussionmentioning
confidence: 76%
“…Although there was no between-group difference in rates of surgery-related complications in Lang and Lo's [13 ]study, the older group had significantly more nonsurgical complications, mainly respiratory, probably due to the larger goiter size and the preoperative airway obstruction. Nevertheless, Rios et al [17] reported that the preoperative symptoms remitted in all patients after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies (Christian Passler et al, 1 Melanie W. Seybt et al, 3 Michael C. Sullivan et al, 4 Ríos A et al 5 and Rodríguez et al 6 ) found that there is no greater risk for thyroid surgery in the elderly. One study (Mekel et al) 7 found a higher increase in morbidity in older group.…”
Section: Discussionmentioning
confidence: 99%